Young Saudi Women Novelists: Protesting Clericalism, Religious Fanaticism and Patriarchal Gender Order. Issue 2 (3rd July 2017) - Kanie, Mariwan
Abstract: From the early 1990s Saudi Arabia witnessed a significant surge in women's writing, especially of novels. This was not a temporary phenomenon but continued into the new millennium, at which time a new generation of young woman novelists emerged who developed a deeper critique of the Saudi state and society than their predecessors in the 1990s. Three well-known and challenging novels are examined: Raja ʾ al-Saniʿ's Banat al-Riyadh [Girls of Riyadh] (2005), Warda Abd al-Malik's Al-awba [Return] (2008), and Samar al-Muqrin's Nisaʾ al-munkar [Women of Vice] (2008). It is argued that a fundamental aspect of these works is their critique of religion, or at least of clerics and their discourse which, in the case of Saudi Arabia, is a profound act. It identifies two approaches by the authors: the individualization of religion and especially the re-articulation of the image of God as a friendly and humanistic God, in contrast to the official discourse; and the development of a strong anti-clerical discourse.